IMPLEMENTASI PROSES REKRUTMEN KARYAWAN PADA PT MERRAS BUSANA JAKARTA SELATAN - Arya Dwitama, Reyndra; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2024)
Human resources (HR) are the most important thing in an organization, both within a company and within an institution. To obtain human resources who have good performance quality and are competent, and in accordance with the company's qualifications, this can be done by carrying out structured recruitment and selection. So the company will get the employees it wants. In this case the researchers involved 55 employees consisting of 55 populations and also 55 samples. The aim of this research is to find out the methods used in the recruitment process at Merras Busana South Jakarta, to find out what the obstacles are in the employee recruitment process at PT Merras Busana South Jakarta, to find out how the process of implementing employee recruitment at Merras Busana Jakarta South. The method used in this research is the observation method and interview method. This comprehensive final assignment aims to understand and study how the employee recruitment process is implemented at PT Merras Busana, South Jakarta. The results of the discussion conclude; 1) The method used by Merras Busana Jakarta is a reference or closed method which only offers to internal company employees. 2) obstacles in the employee recruitment process for PT Merras Busana South Jakarta. The obstacles that exist in the employee recruitment process for PT Merras Busana South Jakarta are the large number of candidates who do not match the criteria and the existence of candidates who are similar to previous candidates due to the limited number of potential applicants. 3) Implementation of the employee recruitment process implemented by PT Merras Busana South Jakarta uses policies or systems that have been created by the company itself